Intraventricular haemorrhage: prevalence and risk factors in babies born with gestational age less than 32 weeks in Malaysian national neonatal registry - Ibrahim , Asma Abolgasim Elmahdi (2017)
Intraventricular haemorrhage (IVH) is a major cause of neurological disabilities in prematures babies, an important cause of mortality and long-term morbidity.This study aimed to determine the prevalence and factors associated with IVH among Malaysian neonates admitted to neonatal intensive care units (NICUs) which participated in Malaysian National Neonatal Registry (MNNR) from 2008- 2011. To determine the prevalence of IVH and associated risk factors among premature babies in Malaysia. To determine the overall prevalence of IVH in hospitals participated in the MNNR from 2008-2011.To compare the prevalence of IVH between the hospitals participated in the MNNR from 2008-2011.To determine the associated risk factors of IVH among preterm infants < 32 weeks admitted to Malaysian NICUs from 2008-2011.To determine the changes in cranial ultrasound (CUS) performed from 2008-2011.This was a cross sectional study. Data from 36 Malaysian hospitals participated in MNNR 2008-2011 electronic database was analysed. The inclusion criteria included neonates with gestational age (GA) < 32 weeks and birth weight (BW) ≤ 1500 grams. Prenatal, delivery characteristic and neonatal events were analysed. Cranial ultrasonography (CUS) was the modality to diagnose IVH. Data entry and analysis conducted using SPSS for window version 22.0. Categorical data were expressed in frequency, percentage, and comparison made using the chi-square test.The level of significance used was p <0.05. Descriptive analysis was done to determine the prevalence of IVH among premature babies. Simple and multiple logistic regression analysis were used to determine the associated factors of IVH.The total babies recruited were 10927 and the prevalence of IVH (overall) in babies whom CUS performed was about 39.5%. Overall, CUS was performed in 85.4% babies. Grade I IVH was 13.7%, Grade II was 12%, Grade III was 8.7% and Grade IV was 4.9%. The prevalence of severe IVH (grade III & IV) was highest in the smallest groups i.e. the GA group 22 - 25 weeks (32.7%) and BW group 500–750gram (29.7%). Prevalence of IVH in East Malaysia hospitals was 40%, West Coast hospitals were 38% and East Coast hospitals was 36 %, p > 0.05. Multiple logistic regression analysis showed that lower GA, lower BW, conventional ventilation, HFOV, pneumothorax, PDA, NEC and infection were significant independent variables associated with IVH. The prevalence IVH among the studied premature babies was 39.5%.Lower GA, BW, conventional ventilation, HFOV, pneumothorax, PDA, NEC, n CPAP, lack of antenatal steroid, maternal diabetic and infection were considered the main associated risk factor with IVH.